Resilience of Sharing Organizational Cultural Characteristics Based on Local Wisdom on Emak-Emak Behavior as a Support Tool for Social Resilience in the Complex in the 5.0 Era - Mulyaningsih, Mulyaningsih (Jurnal Polisci, 2024)
The research aims to determine the commitment of the bureaucracy and technological media to support changes in the cultural climate of local knowledge-based sharing organizations during the pandemic as a form of resilience of the mothers' community in the Nuansa Mas Estate Complex Bandung,West Java,Indonesia during the pandemic.Data was obtained through primary sources which were developed and distributed in the mothers' community among those who experienced/survived COVID-19, families affected by Covid-19 who lived in the Nuansa Mas Estate Complex area,Bandung with 38 participants consisting of 30 respondents and 8 various informants,community and analyzed using mix methods with a survey using SPSS 2003,Nvivo and the convergence approach.The results of the research show that managerial commitment and technology play a major role in supporting changes in the organizational cultural climate of sharing, managerial commitment and technological media capabilities determine a very high average value in changing the organizational cultural climate of sharing as a resilience.Further research can be carried out targeting other countries in Asia or Europe using a quantitative qualitative approach through interviews to obtain more in-depth information based on current state data.